ENVIRONMENTAL ANALYSIS BASED ON CAUSES OF DEATH: A SURVEY - Devi, M. Uma; Vyas, Vishwanand; Agrawal, Nikhil (International Journal of Psychosocial Rehabilitation, 2020)
Every environment has different factors based on which we can analyze the factors such as medical concerns, resource allocations, mortality factors and various others. Information is collected from the analysis of Causes of Death. This helps in analysis of death caused by lack of vaccination, environmental factors, and natural causes. By categorizing the data on the basis of age we can determine the major causes of death in a particular age group which in turn helps hospitals and doctors to prepare accordingly. It will help hospital and healthcare organisations to make better health care decisions and public policy makers to make better policies. A widely used method in the studies of healthcare is statistical method. Though these method are very useful in public health and clinical research policy making, these methods are not capable of finding relation among health condition on their own. Thus we aim to cope with the above challenge by giving input from different datasets and then producing an output which can give more accurate results and better understanding of the situation of the area.